EPISTEMOLOGY OF CORRUPTION AND ECONOMIC CRIME IN NIGERIA DISCOURSE (Journal of Contemporary Issues in Accounting, 2023)
Corruption and all forms of economic and financial crimes in Nigeria are pervasive. All efforts by successive governments to either fight or reduce this humongous menace have proved abortive. It has penetrated all sectors of Nigerian society. Due to government insincerity in fighting corruption and economic crimes in the public sector, civil servants in the ministry of finance take advantage of looting the treasury. The study examined Epistemology of corruption and economic crimes in Nigeria. The objective of the study identified the forms of corruption and types of economic crime in Nigeria, ascertained the extent of corruption and economic crimes and assessed the causes of corruption and economic crimes in Nigeria. The significance of this study will be beneficial to civil servants in the public sector, relevant to law enforcement agencies, public office holders, researchers, bankers, accountants and the general public. The findings of the study is that the long time reign of corruption in the country has impacted negatively on economic growth in Nigeria and It has also decayed or deteriorated the country’s cultural values. The study adopted the Modernization Theory and Game Theory. The study therefore, recommends that the Nigerian government should advance the use of anti-corruption agencies such as; Independent Corrupt Practices Commission (EFCC) to properly investigate corrupt practices and to apportion appropriate sanctions. There should be re-orientation process in education system in Nigeria that would lead to redemption or retrieval and salvaging or restoring of the country’s national character and image.
Keywords: Corruption; Economic Crime; financing crime